Sengketa Pajak Atas Penugasan Pemerintah Pada Perusahaan BUMN (Studi Kasus Pertamina, Pos Indonesia Dan Reasuransi Indonesia Utama) - Sinaga, Raja Darius Sutardjo (UI Scholars Hub, 2024)
State-owned enterprises (BUMN) are legal entities which the government has more than 51% ownership. The purpose of BUMN being established is to carry out national development by seeking profits that can become income for the government as well as carrying out public activities through carrying out public services such as providing telecommunications, electricity, water, and construction of public facilities which cannot be fully fulfilled by the government. Therefore, the government hands over the completion of public services to BUMN to carry them out because of their expertise in their respective fields. In every business process carried out by a legal entity, regardless of its ownership status by the state, there are tax aspects that must be fulfilled. In explanation from the government, there are several BUMN that have defense in the field of taxation. Some of them are regarding tax input on costs incurred in connection with the implementation of state duties, income received from the state and differences in value due to mergers mandated by the state. Therefore, research was carried out on how BUMN defended themselves in the dispute and what the judge's opinion was regarding the dispute that occurred.